Alternative dispute resolution and domestic violence : women, divorce and alternative justice - Lavi, Dafna (Routledge Taylor and Francis Group, 2018)
"Dealing with the interface between the Alternative Dispute Resolution (ADR)movement and the phenomenon of domestic violence against women, this book examines the phenomenon of divorce disputes involving violence through the prism of alternative justice and the dispute resolution mechanisms offered by the ADR movement. This book is the first academic treatise presenting the theoretical underpinnings of the correlation between the ADR movement and divorce disputes involving violence, and the potential contribution of this movement to the treatment of disputes of this nature. Through mapping the main values of the ADR movement, the book proposes a theoretical-analytical basis for understanding the inability of the legal system to deal with disputes of this nature, alongside a real alternative, in the form of the ADR mechanisms."--Provided by publisher.